1996
DOI: 10.1136/vr.139.15.360
|View full text |Cite
|
Sign up to set email alerts
|

Protein markers in cerebrospinal fluid from BSE‐affected cattle

Abstract: Two-dimensional gel electrophoresis was used to analyse cerebrospinal fluid (CSF) from 75 suspect cases of bovine spongiform encephalopathy (BSE), 61 of which were confirmed by post mortem brain histopathology, and 38 normal cattle. CSF samples were also examined from cattle killed at periodic intervals through the incubation period following experimental challenge. Consistent changes were recorded in all CSF samples from the confirmed cases of natural BSE and also from cattle showing early signs of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In previous studies, the ApoE protein has been proposed as a biomarker for prion diseases [48], [49], [50], [51] in addition to its role in the Alzheimer's disease pathway [52], [53]. Several studies have also reported the involvement of many members of the apolipoprotein gene family ( ApoA1 , ApoA4 , ApoC1 , ApoC2 , ApoC3 and ApoD ) in transmissible spongiform encephalopathies [26], [30], [54], [55].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the ApoE protein has been proposed as a biomarker for prion diseases [48], [49], [50], [51] in addition to its role in the Alzheimer's disease pathway [52], [53]. Several studies have also reported the involvement of many members of the apolipoprotein gene family ( ApoA1 , ApoA4 , ApoC1 , ApoC2 , ApoC3 and ApoD ) in transmissible spongiform encephalopathies [26], [30], [54], [55].…”
Section: Discussionmentioning
confidence: 99%
“…They were based on work done in the 1980s by Harrington and others (1986), in which brain proteins of the 14-3-3 group were related to the presence of CJD. The initial optimism about the use of CSF in clinical cases of BSE (Jones andothers 1996, Lee andHarrington 1997) has declined and, because the markers are probably connected with pathological changes in the central nervous system itself, it is unlikely that this approach will be successful in preclinical stages, though it may have potential in the early clinical stages (Jones and others 1996). colleagues (1980, 1982) used a mouse bioassay to show that infectivity was detectable in the lymphoid tissue of naturally infected scrapie sheep as early as 10 to 14 months of age, well before it occurred in the central nervous system (cNs).…”
mentioning
confidence: 99%
“…and Jones et al . 11, 17. For 57 of the 66 identified gene products reported here, the presence of homologous proteins in human CSF has been reported 3, 24.…”
Section: Bovine Csf Proteins Identified In This Studymentioning
confidence: 60%
“…Proteins representing 66 genes, 58 of which have not been identified on any previously published bovine CSF map 11, 17, were identified as constituents of the bovine CSF (Fig. 1).…”
Section: Bovine Csf Proteins Identified In This Studymentioning
confidence: 97%